Comparative Analysis of E5–E15 Fuel Blends and 10–14 g CVT Roller Mass on the Power–Torque Curves of a 110 cc Automatic Motorcycle - Hermawan, Muhammad Vendy; Andriyansyah, Deni; Safarudin, Muhammad Ilyas (Institut Teknologi Adhi Tama Surabaya, Indonesia, 2026)
This study aims to evaluate the combined effects of low level ethanol blending and CVT roller mass variation on the power and torque characteristics of a 110 cc automatic motorcycle. Experiments were conducted using two Pertalite–ethanol fuel blends, E5 and E15, in combination with CVT roller masses ranging from 10 g to 14 g. Engine performance was evaluated using a dynotest, enabling direct measurement of the power–rpm and torque–rpm characteristics for each fuel–roller configuration. The results indicate that increasing the ethanol content from 5% to 15% leads to a consistent improvement in engine performance across the tested range. Compared with E5, the E15 blend produces higher peak power and torque while maintaining the performance peak within the mid range engine speed region that is favorable for CVT operation. Among the tested configurations, the combination of E15 fuel with an 11 g roller delivers the best overall performance, achieving a maximum power of 8.94 hp at approximately 7,200 rpm and a peak torque of 9.21 Nm at around 7,000 rpm. In contrast, heavier rollers tend to reduce peak torque and shift the effective power band toward higher engine speeds, which is less beneficial for daily riding conditions. These findings demonstrate the interaction between fuel blending and CVT roller mass in shaping the power–torque characteristics of automatic motorcycles and provide practical guidance for optimizing performance under everyday operating conditions.